Pengkonsepsian dan pemetaforaan "hati" (Jurnal Bahasa, 2005)
The "heart" has been acknowledged as the seat of emotions in many languages. However, previous studies (Asniah, 1996; Goddard, 2001) have argued that in Malay, the part of the body that is the most pro-ductive in terms of emotions is not the heart "jantung" but the liver "hati". This paper offers an alternative view by exploring various conceptualizations and meatphorization of hati and activities related to this internal organs in Malay. In particular, this paper examines the various metaphorization of emotions in terms of hati [liver] following a Lakoffian type analysis. Our analysis of a Malay corpus reveals sev-eral categories of metaphorization of emotions related to "hati". The first is action that affects the hati. This is represented by action verbs such as hiris [to slice thinly] , cengkam [to grip firmly] and gores [to scratch] etc. and the resulting hurt felt by the hati. Secondly, and closely related to the first is illness of the hati (e.g. sakit hati [lit. sick liver]). The illness of the hati results in anger which is caused by various fac-tors such as actions, words etc. The third category is emotion felt as exemplified by possession of hati. The possession of hati is signaled by words such as ambil [take] , menawan, menakluk [conquer] as in menawan hati/"win over the heart". The final type relates to hati "be-ing in charge" of emotions as in ikut hati [lit follow the liver] . The usage of hati in this category exemplifies the central position of the liver in expressing emotions. Apart from the categories above, the schematic metaphorizations of hati found in the corpus include the con-tainer metaphor, hati as the nursery for the seeds of emotion, hati as source of piety, determination, desire and also as the inner voice or inner self and consciousness.